COVID-19 Pandemic Awareness, Attitudes, and Practices Among the Pakistani General Public - Rehman, Rehana; Jawed, Shireen; Ali, Rabiya; Noreen, Khola; Baig, Mukhtiar; Baig, Javaria (Frontiers in Public Health, 2021)
Background: Outbreak of COVID-19, in many countries, has imposed a lockdown on their residents. The usefulness of extenuative actions is extremely reliant on society's knowledge, attitudes, and practices (KAP) toward pandemic control. Objective: This study aimed to explore the awareness, attitudes, and practices of the general Pakistani population to COVID-19. Methods: From June 13, 2020, until June 30, 2020, a cross-sectional online KAP survey was conducted among the Pakistani public. For data collection, a validated self-administered questionnaire was used. The survey instrument consisted of six demographic characteristics, 14 items on knowledge, four on attitudes, and six items on practices, modified from a previously published questionnaire on COVID-19. Results: The present study included 2,307 participants, 58.3% males and 41.7% of females. The majority (86.7%) sought information from social media (SM) and television, 95% had good practices, 89.9% had positive attitudes, and two-thirds (67.4%) of the respondents had adequate knowledge. The students and people from younger age groups had more positive attitudes compared with others. Highly educated w with other groups (p < 0.001). In logistic regression analysis, the odds ratio indicated that the private job was negatively associated, and high monthly income was positively associated with adequate knowledge (OR = 0.595). Old age was the predictor of negative attitude, and high school degrees and master's degrees were associated with good practice scores. Conclusion: The Pakistani general population has an overall positive attitude and proactive practices against COVID-19, but their knowledge is inadequate. The most important source of information was SM, followed by television. These are playing a crucial role in educating the Pakistani public.